PSIKOLOGI PERKEMBANGAN MORAL: INTEGRASI TEORI LAWRENCE KOHLBERG DAN IMAM AL-GHAZALI DALAM KURIKULUM PENDIDIKAN AGAMA ISLAM - Ikhlasul Akmal; Muslim Afandi; Mhd Subhan (STKIP Subang, 2026)
Islamic Religious Education (PAI) faces significant challenges in fostering students' moral character due to the limited integration of cognitive development, moral reasoning, and spiritual formation within the learning process. This study aimed to analyze Lawrence Kohlberg’s theory of moral development and Imam Al-Ghazali’s concept of spiritual education and to examine their relevance to the development of the Islamic Religious Education curriculum. Employing a qualitative library research approach, the study utilized content analysis and comparative conceptual analysis to synthesize primary and secondary literature in educational psychology and Islamic education. The findings reveal that Kohlberg’s theory emphasizes the progressive development of moral reasoning through cognitive maturation, whereas Al-Ghazali’s educational philosophy highlights the purification of the soul (tazkiyat al-nafs), moral habituation, and spiritual cultivation as the foundation of character formation. The comparative analysis demonstrates that these two perspectives are complementary and can be integrated into a holistic educational framework that balances cognitive, moral, and spiritual dimensions. This integrative model provides a conceptual foundation for developing a more adaptive and comprehensive PAI curriculum that aligns with students’ psychological development while promoting intellectual competence, moral responsibility, and religious character in contemporary educational contexts.